Repairing attachment in families with depressed adolescents: A task analysis. - Stern, Richard S.; King, Ashley A.; Diamond, Guy (Journal of Clinical Psychology, 2023)
Aims: This exploratory pilot study (N = 3 sessions, 793 speech units) used task analysis to refine an early model of the attachment task in attachment‐based family therapy (ABFT). The attachment task aims to repair long‐standing parent–adolescent relational ruptures that inhibit parents from being a resource for adolescents recovering from depression and/or suicidality. Methods: Video recordings of three attachment task sessions with strong adherence to the model were selected for intensive study. Two sessions were rated as successful (i.e., attachment was repaired) and one as unsuccessful (i.e., attachment repair did not occur). Sessions were then coded using Structural Analysis of Social Behavior (SASB). Results: The current SASB analysis provided empirical support for our previous clinical impression that the task involves three parts: (I) adolescent disclosure of attachment rupture, (II) parent disclosure, and (III) a more mutual conversation. SASB also provided insights into more subtle elements of the model. Conclusion: Successful attachment sessions were associated with high parent affiliation and autonomy—both while affirming the adolescent's story and when disclosing their own experience. Unsuccessful task attempts were associated with parental enmeshment and hostile belittling, blaming, and distancing. An enhanced model of ideal parent behaviors during the attachment task is offered, including space for parent disclosure—perhaps even apology—that is both warm and independent, leading to a more mutual parent–adolescent conversation. Clinically, the findings support the importance of the therapist focusing on the process and quality of parent–child interactions to facilitate attachment repair.